Gender and Economic Growth in Kenya : Unleashing the Power of Women - Ellis, Amanda; Cutura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (Washington, DC: World Bank, 2012)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, "Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment," this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya's Economic Recovery Strategy for Wealth and Employment Creation 2003-2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.